THE PATH FROM INDUSTRIAL INSTITUTE TO NATIONAL RESEARCH UNIVERSITY - A. Kh. Gilmutdinov (Высшее образование в России)
Interview with the Rector of Kazan National Research Technical University named after A.N. Tupolev – KAI A.Kh. Gilmutdinov.